Problems Faced by Women Entrepreneurs in Ernakulam District, Kerala - Manjula R. Iyer (Commerce Spectrum, 2018)
Women Entrepreneur is a person who accepts challenging role to meet her personal needs and become economically independent. The state of Kerala is the industrially developing area in which some of the entrepreneurs excel in small scale industry. Even though the Government organizes women by various associations, they are not ready to undertake the business. As compared to men, women are less motivated to start business units due to some unwanted fear and lack of motivation. The principal aim of the study is to identify the major problems faced by women entrepreneurs in Ernakulam District, Kerala. For the purpose of study, primary data were collected from 90 women entrepreneurs in Ernakulam district and simple statistical tools were used for data analysis. The study revealed that the major problems faced by women entrepreneurs in the District were financial constraint, Inadequate Institutional support, Problems in Marketing, Social Attitude, Non-availability of good workers/employees etc.